PENGARUH AKLIMATISASI KADAR GARAM TERHADAP NILAI KEMATIAN DAN TINGKAH LAKU IKAN GUPPY (POECILIA RETICULATA) SEBAGAI PENGGANTI UMPAN IKAN CAKALANG (Katsuwonus Pelamis) - Muhammad Zainuddin Lubis; Sri Pujiyati (Fakultas Perikanan dan Ilmu Kelautan, 2013)
Acclimatization is physiological adaptation way or a way from a species to adjust itself with new environment. The purpose of this research is to observe the process of salt level acclimatization in Guppy fish (Poecilia reticulate). Salt level about 2 g/mol was added in the water or environment until the salinity is 30 ‰. Guppy fish males have a body size 5 cm, colour schemes the body and fins are very bright and has a very economical price so as to attract the attention of Tuna (Katsuwonus pelamis).That process was done by adding 720 g of salt level each day during 14 days. In the first day, 65 Guppy fishes with average of weight is 1,1 gram and total length is 2,5 cm was added in the water. During 8 days (salinity 18 ‰), Guppy fish can adjust itself with the environmental, however after 8 days mortality rate of the fish is 0,02% - 0,05%. Until the end of the research, the mortality rate is 0,13% (9 fishes). Fish test results conducted in the waters of Pramuka Island, thousand islands, showed fish can swim well and always be in the surface waters without sight change very significant.